Market Reform in Society : Post-Crisis Politics and Economic Change in Authoritarian Peru - Arce, Moises (Book collections on Project MUSE., 2005)
"Going beyond the usual state-centric approach to the study of the politics of neoliberal reform, Moises Arce emphasizes the importance of understanding the interaction between state reformers and collective actors in society. In Market Reform in Society he focuses our attention on how various societal groups are affected by different types of reform and how their responses in turn affect the state's subsequent pursuit of reform."--Jacket